Impact of the Ebola virus disease outbreak (2014-2016) on tuberculosis surveillance activities by Guinea's National Tuberculosis Control Program: a time series analysis - Aboubacar Sidiki Magassouba; Boubacar Djelo Diallo; Lansana Mady Camara; Kadiatou Sow; Souleymane Camara; Boubacar Bah; Alpha Oumar Barry; Thierno Hassane Diallo; Aboubacar Camara; Adama Marie Bangoura; Oumou Younoussa Sow (BMC, 2020)
Abstract Background Most countries in Subsaharan Africa have well-established National Tuberculosis Control Programs with relatively stable routine performances. However, major epidemiological events may result in significant disruptions. In March 2014, the World Health Organization announced the outbreak of Ebola virus disease in Guinea, a country with a high incidence of TB and HIV. Our study aimed to assess the impact of the Ebola virus disease outbreak on TB notification, treatment, and surveillance, using main indicators. Methods This is a retrospective cohort study that compared TB trends using surveillance data from the periods before (2011-2013), during (2014-2016), and after (2017-2018) Ebola virus disease outbreak. A time-series analysis was conducted to investigate the linkages between the decline in TB notification and the Ebola virus disease outbreak through cross-correlation. The lag in the cross-correlation test was evaluated using ANCOVA type II delayed variable dependent model. The surveillance system was assessed using TB surveillance standards and benchmarks and vital registration systems recommended by WHO, compared with those of 2015 during the Ebola virus disease. Results The rate of reporting of TB declined from 120 cases per 100,000 in 2011 to 100 cases per 100,000 in 2014, at the peak of the Ebola virus disease outbreak. The time-series cross-correlation test of all notified cases of TB and Ebola showed a significant lag of − 0.4 (40%), reflecting a drop in the rate of notification (F-value = 5.7 [95% CI: 0.2-21.3]). The Ebola virus disease had no negative impact on patient treatment outcomes (F-value = 1.3 [95% CI: 0.0-8.8]). Regarding the surveillance system, five out of 13 WHO standards and benchmarks were met following their evaluation in 2019, after the Ebola virus disease outbreak, compared to three in 2015. Conclusion Major epidemics such as the Ebola virus disease outbreak may have a significant impact on well-established TB control programs as shown in the example of Guinea. Sudden disruptions of routine performance may lead programs to improve their surveillance system. The experience acquired in the fight against EVD and the investments made should make it possible to prepare the health system in a coherent manner for the other probable episodes.